Dampak Bullying Bagi Kesehatan Mental Di Universitas - Pratama, Dendy Suma; Putri, Balqis Dwi Ananda; Hosnah,SH.,MH., Dr.Hj.Asmak Ul (PT. Sharia Journal and Education Center, 2024)
ABSTRACT Bullying in the university environment has become a problem that has a serious impact on students' mental health. This study aims to identify the impact of bullying on students' mental health at university and explore the factors that influence the intensity of this impact. Bullying that occurs in universities can be verbal, physical, social, or even through digital media (cyberbullying). The effects of bullying can include a variety of mental problems, such as anxiety, depression, stress, and decreased self-confidence, which ultimately affect students' academic performance and social interactions. In the university environment, students are often faced with a variety of complex academic and social pressures. In the midst of the adaptation and self-development process, some students experience bullying, both from fellow students and from other social environments. This phenomenon leads to various psychological impacts that disrupt students' mental balance and can interfere with their academic success and well-being in the future. Key words: bullying, mental health, students, university, cyberbullying ABSTRAK Bullying di lingkungan universitas telah menjadi masalah yang berdampak serius bagi kesehatan mental mahasiswa. Penelitian ini bertujuan untuk mengidentifikasi dampak bullying terhadap kesehatan mental mahasiswa di universitas serta menggali faktor-faktor yang memengaruhi intensitas dampak tersebut. Bullying yang terjadi di universitas dapat berupa kekerasan verbal, fisik, sosial, atau bahkan melalui media digital (cyberbullying). Efek dari bullying ini dapat mencakup berbagai masalah mental, seperti kecemasan, depresi, stres, dan penurunan kepercayaan diri, yang pada akhirnya berpengaruh terhadap kinerja akademik dan interaksi sosial mahasiswa. Di lingkungan universitas, mahasiswa sering dihadapkan pada berbagai tekanan akademik dan sosial yang kompleks. Di tengah proses adaptasi dan pengembangan diri, beberapa mahasiswa mengalami tindakan bullying, baik dari sesama mahasiswa maupun dari lingkungan sosial lainnya. Fenomena ini memunculkan berbagai dampak psikologis yang mengganggu keseimbangan mental mahasiswa dan dapat mengganggu keberhasilan akademik serta kesejahteraan mereka di masa depan. Kata kunci : bullying, kesehatan mental, mahasiswa, univesitas, cyberbullying